The communication of local social actors on the environment in Algeria. Sociological reflections on the communication of environmental consultation: Case of the Kabyle region - SADOUNI, Tewfik (Journal of Human Sciences, 2020)
Algeria has launched a land-use plan for a decade to ensure a territorial balance between the different regions. As a result, new large infrastructures were submerged but their implementation policies spawned. However, several social movements were noticed because of the unacceptability of local residents of an urban project or an environmental project not concerted.For this, recourse to public consultation, upstream, has become a primary obligation. In this article, our work focuses on analyzing the communication and consultation process established between the different social actors involved in the decision-making process in the Kabyle region, specifically in the Bouira region.